2a+3b=-1
a-3b=4
=======
3a=3
a=1
1-3b=4
-3b=3
b=-1
The solution set is (1,-1)
Check:
2(1)+3(-1)=-1
2-3=-1
-1=-1
1-3(-1)=4
1+3=4
4=4
I hope this helps!
2007-01-27 13:54:08
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
2a + 3b = -1
+ a - 3b = 4
--------------------
3a + 0 = 3
a = 3/3
a = 1
Substituting for a and solving for b
2(1) + 3b = -1
2 + 3b = -1
3b = -1 - 2
3b = -3
b = -3/3
b = -1
Substituting and verifying
a - 3b = 4
1 - 3(-1) = 4
1 - -3 = 4
2a + 3b = -1
2(1) + 3(-1) = -1
2 + -3 = -1
a = 1, b = -1
2007-01-27 21:57:08
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
2a+3b=-1
a - 3b = 4
You should be able to see that when you add the two equations, the 3b terms disappear and you are left with:
a+2a = -1 +4
3a = 3
a=1
Now put a =1 in the 2nd equation getting:
1-3b=4
-3b= 3
b=-1
2007-01-27 21:57:48
·
answer #3
·
answered by ironduke8159 7
·
0⤊
0⤋
2a + 3b = -1
+ a - 3b = 4
------------------
3a + 0b = 3
3a = 3
First: isolate "a" on one side > divide both terms by "3"...
3a/3 = 3/3
a = 1
Sec: replace "1" with the "a-variable" (either equation) in the 1st equation...
2(1) + 3b = -1
2 + 3b = -1
*Subtract "2" from both sides...
2 - 2 + 3b = -1 - 2
3b = -3
Third: isolate "b" on one side > divide both terms by "3"...
3b/3 = -3/3
b = -1
Solution: (1,-1)
2007-01-27 23:43:59
·
answer #4
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
add the equations together:
2a+3b=-1
a-3b=4
3a+0b=3
a=1
Now put 1 in the equation for a
2(1)+3b=-1
3b=-3
b=-1
2007-01-27 21:55:31
·
answer #5
·
answered by Ben B 4
·
0⤊
0⤋
Add the second equation to the firt and get 3a=3, from which you can determine that a=1. Next substitute a=1 into either of the above equations to get b=-1.
2007-01-27 21:52:22
·
answer #6
·
answered by bruinfan 7
·
1⤊
0⤋